Viscous Dissipation Effects on MHD Natural Convection Flow along a Sphere (Journal of Mechanical Engineering, 2008)
In this paper, we describe the viscous dissipation effects in magnetohydrodynamic (MHD) natural convection flow on a sphere. The natural convection laminar flow from a sphere immersed in a viscous incompressible optically thin fluid in the presence of magnetic field has been investigated. The governing boundary layer equations are first transformed into a non-dimensional form and the resulting nonlinear system of partial differential equations are then solved numerically using a very efficient finite-difference method with Keller-box scheme. Here we have focused our attention on the evolution of shear stress in terms of the local skin friction and the rate of heat transfer in terms of local Nusselt number, velocity profiles as well as temperature profiles for some selected parameters consisting of magnetic parameter M, viscous dissipation parameter N and the Prandlt number Pr.Keywords: Viscous dissipation, magnetohydrodynamics, natural convection, Nusselt number. Journal of Mechanical Engineering Vol.36 Dec. 2006 pp.44DOI = 10.3329/jme.v36i0.810